2021
DOI: 10.1088/1402-4896/ac07b7
|View full text |Cite
|
Sign up to set email alerts
|

Supernonlinear wave and multistability in magneto-rotating plasma with (r, q) distributed electrons

Abstract: Supernonlinear ion-acoustic waves (IAWs) and their multistability are studied under the Zakharov-Kuznetsov (ZK) and modified ZK (mZK) equations in a rotating magnetized electron-ion plasma that consists of generalized (r, q)-distributed electrons. Bifurcation of IAW is presented through phase plane analysis and existence of IAW solutions is also shown through graphs of potential energy function. Supernonlinear wave exists for system corresponding to mZK equation with nonlinear periodic and solitary wave soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 84 publications
1
10
0
Order By: Relevance
“…In the ion-acoustic waves, inertias of the electron and positron are neglected, and the electron and positron fluids can be separately in equilibrium with an electrostatic potential j. For such a plasma model, the nonlinear dynamics of low-frequency ion-acoustic waves are governed by the following equations [1,2,5,41],…”
Section: The Plasma Model and Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the ion-acoustic waves, inertias of the electron and positron are neglected, and the electron and positron fluids can be separately in equilibrium with an electrostatic potential j. For such a plasma model, the nonlinear dynamics of low-frequency ion-acoustic waves are governed by the following equations [1,2,5,41],…”
Section: The Plasma Model and Governing Equationsmentioning
confidence: 99%
“…Propagation of ion acoustic solitary waves (IASWs) is usually related to the plasma compression. For this reason, more solitary wave properties are obtained from the compressive/rarefactive waves in multi-component magnetized [1][2][3][4] or unmagnetized [5][6][7] plasmas by using the pseudo potential approach and the reductive perturbation method, i.e., Korteweg-deVries (KdV) soliton [8,9], in the linear [10] and nonlinear dynamics [11,12]. It has been revealed that the KdV soliton are formed due to a balance between dispersion and nonlinearity in the plasma.…”
Section: Introductionmentioning
confidence: 99%
“…5. It is noted that in small amplitude approximation the behavior and property of the nonlinear periodic and super-periodic waves propagating in different plasma systems are extensively studied by means of the bifurcation technique [28][29][30]. In case of arbitrary amplitude, the existence and propagation of nonlinear periodic and super-periodic solutions in our plasma system is in progress considering the impact of some relevant plasma parameters on the features of such waves.…”
Section: Double-layer and Supersoliton Analysismentioning
confidence: 99%
“…On the other side, in some limiting cases another type of nonlinear waves called periodic and super-periodic waves arise. The occurrence of such types of waves has been extensively studied by several authors [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Lately, the critical point has also been taken care of and in such a case one obtains Gardner equation which involves both the quadratic and cubic nonlinearities. Many researchers have explored these equations and their versions in the higher dimensions in the recent past (Mannan and Mamun, 2011;Masud et al, 2012;Abdikian et al, 2020;Nawaz et al, 2021;Nawaz et al, 2022).…”
Section: Introductionmentioning
confidence: 99%